The Rancièrian Regime: Politics and Aesthetics around 1800 (KULT_online, 2010)
Ästhetische Regime um 1800 (Aesthetic Regimes around 1800), edited by Friedrich Balke, Harun Maye and Leander Scholz, explores the interrelation between politics and aesthetics. The majority of assembled essays builds on Jacques Rancière’s concept of an “aesthetic regime of art”. Rancière’s approach is the source of a divide in academic circles: some celebrate his philosophy while others disregard it as an academically questionable trend. The present volume surmounts polarisation and offers a critical yet extremely productive examination of Rancière’s theory. The compendium closes with an original contribution of Rancière which merges several of his key studies and already includes reflections on critical voices.